Indicators of water quality and land usage patterns in watersheds in the state of Paraná, Brazil - Gonçalves, Daniel Ruiz Potma; Rocha, Carlos Hugo (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to determine the relationship of water quality indicators with rainfall regime and land use patterns. Four watersheds and their respective permanent protected areas (APPs), sources of the Alagados reservoir, in the state of Paraná, Brazil were evaluated. Land use at basin level and in the APPs were mapped in a geographic information system environment, and the resulting patterns were evaluated as to their relation with the water quality index (IQA) and rainfall regime. Water quality decreased in the summer periods, when higher average rainfall and more intensive land management were present, with larger cultivated areas in the landscape. Total cultivated area in the APPs had negative effect on water quality. Differences in topography, geomorphology, and soil types, as well as their effect on land use patterns, were discussed as a potential explanation for the observed values of the IQA in each basin. The variability of the IQA patterns among watersheds, as well as the extreme values observed according to the season, highlights the demand for land use planning, particularly within the APPs, in order to ensure desirable patterns of water flow and quality in the wellspring.